Pengaturan Status Pada Jabatan Notaris Saat Mencalonkan Diri Sebagai Anggota Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten/Kota - Yogaswara, Achmad Yudha; Yusa, I Gede (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 01 (2023)DO - 10.24843/AC.2023.v08.i01.p10, 2023)
This paper aims to find out how the legal arrangements regarding notaries, regional people's representatives and concurrent positions, as well as the legal status of a notary who is running for a member of the regional people's representative council, whether to take leave or not to practice. The research method used is normative law, a method by using an approach through legislation then a conceptual approach, along with sourced from primary legal materials and then secondary legal materials. The result of the discussion of this paper is that based on the explanation of Article 17 letter d of the UUJNP, a notary who is elected as a member of the regional people's representative council, the notary must apply for leave, and appoint a substitute notary.